Sistem Klasifikasi Tingkat Kelayakan Lahan Tanaman Padi Menggunakan Pengujian Naïve Bayes Dan K-Nearest Neighbor Di Kabupaten Aceh Utara Berbasis Web - Pratama, Angga; Susanti, Eka; Faridhatul Ulva, Ananda (Jurnal Tika, 2022)
Cultivation of food crops has a significant role in the lives of Indonesian citizens, especially to fulfill their daily food needs. Efforts to cultivate rice plants often face obstacles, one of which is in ensuring the suitability of the soil, therefore the determination of the land at the planting stage or the land to be selected is not suitable land (unproductive), so that agricultural yields will not be maximum and will cause losses (financial). which is pretty big. The goal to be obtained in the concept of a classification system for the level of feasibility of rice plant land is to make it easier for farmers, residents and governments to make decisions by determining the feasibility of rice plant land. The method used in the classification system for decision support is the Naïve Bayes and K-Nearest Neighbor testing methods for comparison in efficient decision making. In rice, it is adjusted by calculating the value of criteria such as land characteristics, namely air temperature, rainfall, humidity, soil texture, pH, drainage and soil height. The results help farmers to make it easier to analyze land conditions for rice plants and increase rice production yields in North Aceh Regency